Performance and Memory: The Trans-canada Highway And The Jumping Pound Grade Separator, Alberta - White, Stephanie (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2002)
RésuméThe Trans-Canada Highway (1949-1962) was a major postwar Canadian nationalist project. It is also a real roadway, originally constructed to standards acceptable in 1949, and paid for by the provinces and the federal government. It is a clear case of a material object designed under a set of conditions that evolve, adapt and persist through changing circumstances. The highway’s physical materiality and usefulness ensures its continued presence; its political and social readings are more ephemeral. Its ambitions of sovereignty were a response to American concerns over geopolitical security. Its routing was a response to American tourism. Its structures — bridges, overpasses, guard rails, verges, signage — are at once intensely local, sited in very particular landscapes, and at the same time follow the lineaments of abstract expressionism — overtly the quantifiable universalism of the modern movement. The Trans-Canada Highway is a case of modernism coming to ground in a local geography.